TINGKAT PEMAHAMAN PASIEN OPERASI TERHADAP PENJELASAN INFORMED CONCENT - Pinondang Hotria Siregar (LPPM Universitas Abdurrab, 2024)
An explanation of informed consent for medical actions is one of the very important things before an operation is performed. In its implementation, every hospital must have standard procedures as a reference. From an initial survey in February 2019 of patients and their families who had undergone surgery, the provision of informed consent was still not in accordance with the applicable procedures. Out of 30 people, 12 (40%) did not understand the content of the medical information conveyed by the doctor regarding risks, complications, and surgical actions. This research design uses an analytic cross-sectional survey aimed at determining the factors that influence patients' understanding of the explanation of informed consent for surgery at RS Vita Insani Pematangsiantar. The population consists of patients and families representing patients who have undergone major surgical procedures. Sampling was done using the total sampling method, totaling 223 people. Data collection was conducted using a questionnaire. Data analysis using univariate, The results of the study showed that the level of patient understanding of Explanation of informed consent operations in the understanding category (97.3%). The conclusion is that the level of patient understanding of the explanation of informed consent surgery is in the category of understanding and the factor that significantly affects the patient's understanding is the information access factor in the form of information delivery time. The advice given is that in providing an explanation of informed consent, it is necessary to pay attention to the time of submission of the information and must refer to the provisions that have been specified